Interactions between arsenic exposure, high-fat diet and NRF2 shape the complex responses in the murine gut microbiome and hepatic metabolism - Schiro, Gabriele; Liu, Pengfei; Dodson, Matthew; Zhang, Donna D.; Ghishan, Fayez K.; Barberán, Albert; Kiela, Pawel R. (Frontiers in Microbiomes, 2022)
Inorganic arsenic (iAs) exposure has been associated to various detrimental effects such as development of metabolic syndrome and type 2 diabetes via oxidative stress and induced prolonged activation of the NRF2 transcription factor. Such effects can be aggravated by poor dietary habits. The role of gut microbiota in promoting metabolic changes in response to arsenic has yet to be precisely defined. To address the complexity of the interactions between diet, NFE2L2/NRF2, and gut microbiota, we studied the chronic effects of iAs exposure in wild-type (WT) and Nrf2-/- mice fed normal (ND) vs. high-fat diet (HFD), on the gut microbial community in the context of hepatic metabolism. We demonstrate that all treatments and interactions influenced bacteria and metabolic profiles, with dietary differences causing a strong overlap of responses between the datasets. By identifying five metabolites of known microbial origin and following their fate across treatments, we provide examples on how gut microbial products can participate in the development of iAs and HFD-induced metabolic disease. Overall, our results underline the importance of the microbial community in driving gut-liver-cross talk during iAs and HFD exposure.